Exploring a Multivalent Approach to α‐L‐Fucosidase Inhibition1. Issue 32 (19th September 2013) - Moreno‐Clavijo, Elena; Carmona, Ana T.; Moreno‐Vargas, Antonio J.; Molina, Lidia; Wright, Daniel W.; Davies, Gideon J.; Robina, Inmaculada
Abstract: To probe the utility of a multivalent approach for fucosidase inhibition, a series of di‐ and tri‐valent imino sugars based onL ‐fuco ‐configured 1, 4‐imino‐ and 1, 4‐bis(imino)‐cyclitol epitopes has been synthesized and analyzed for fucosidase inhibition with the best trivalent species yielding a modest improvement in binding constant. Structural analysis of a representative pair of mono‐ and tri‐valent imino sugars has been performed on a bacterial fucosidase, Bt Fuc2970. The 3D structures show binding of the imino‐cyclitol in the 3 E conformation, consistent with the known pathway for fucosidase action. Abstract : Di‐ and tri‐valent imino sugars based on L ‐fuco ‐configured 1, 4‐imino‐ and 1, 4‐bis(imino)‐cyclitol moieties present α‐L ‐fucosidase inhibitory activities in the μM and nM range.